PH effect of coagulation bath on the characteristics of poly(acrylic acid)-grafted and poly(4-vinylpyridine)-grafted poly(vinylidene fluoride) microfiltration membranes - Ying, L. (2014)
10.1016/S0021-9797(03)00507-1